Strategi Peningkatan Kesejahteraan Pekerja Migran Indonesia (PMI) Purna Wanita Melalui Program Desmigratif - Dwiningwarni, Sayekti Suindyah; Suyanto, Suyanto; Dwi Andari, Syamsiyah Yuli (CV. ITTC INDONESIA, 2025)
Government's strategy to improve the welfare of Female PMI Returnees. The research method is mixed in the form of sequential exploration. The data used are primary and secondary data. The results of the study, first, are the need for regional government policies related to improving the welfare of Female PMI Returnees. Second, it is necessary to open employment opportunities in the informal sector. Third, it is necessary to manage the PMI Returnee database in an integrated manner starting from the Central, Provincial, Regency and Village Governments. The results of the SWOT analysis show that there are three strategies needed to improve the welfare of Female PMI Returnees through Desmigratif. This study concludes that there is still a need for partnerships between the district government, village and PMI Returnees